Proteasome inhibitors: beyond NFKB inhibition alone and the emerging role of combination therapy in the treatment of multiple myeloma (Hematology Meeting Reports, 2009)
Introduction The emerging role of novel agents has dramatically increased treatment options for patients with multiple myeloma (MM), with new agents including thalidomide, bortezomib and lenalidomide significantly improving outcomes for patients with both newly diagnosed and relapsed and refractory MM.1-5 Studies in early relapse suggest that both bortezomib and lenalidomide are more effective in patients who have received fewer prior therapies and provide a rationale to investigate their use in the frontline setting.6,7 As an example, the ability to safely combine bortezomib with other combinations and the consistent signal provided by informative pre-clinical studies has led to a number of important combination strategies in both the upfront and the relapsed and relapsed/refractory settings (Figure 1). The role of NFKB as a key therapeutic target has thus been validated, and beyond NFKB the importance of other downstream targets has become established, as combination therapies have shown activity even in highly resistant MM.8,9 Early clinical studies with small molecules and monoclonal antibodies have likewise demonstrated that there are a number of promising new agents in clinical development that when combined with established platforms of bortezomib- based therapies may provide additional treatment options for patients with relapsed and refractory disease.